Protocol for the Use of a Novel Bioreactor System for Hydrated Mechanical Testing, Strained Sterile Culture, and Force of Contraction Measurement of Tissue Engineered Muscle Constructs - Somers, Sarah M.; Grayson, Warren L. (Frontiers in Cell and Developmental Biology, 2021)
Bioreactor systems are built as controlled environments for biological processes and utilized in the field of tissue engineering to apply mechanical, spatial, and chemical cues to developing tissue grafts. Often the systems are applied to instruct differentiation and maturation of the cells grown inside. Perhaps the most obvious targets for strain and compression-based bioreactors are mechanically active tissues, as it is hypothesized that biomimetic mechanical environments instruct immature cells to form differentiated tissues. One such tissue, skeletal muscle, has been identified as a key candidate for strain application due to the close structure-function relationship of myofibers. Here we detail the multiple uses of our custom-built bioreactor system in combination with electrospun fibrin microfibers for muscle tissue engineering. Outlined below are the methods used in our system to test the mechanical properties of our hydrogel-based scaffolds in an aqueous environment, including Young’s modulus and poroelasticity. Additionally, we demonstrate the application of tensile strain to sterile cell cultures grown on electrospun scaffolds and perform end-point testing of tissue contractility with the addition of an electrode.